Referring Expression in Black Mirror (Season 3 Episode 1: “Nosedive”): Pragmatics Study - Amira Bellita Runadi; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze and investigate the various forms of referencing expressions and their meanings in the serial movie Black Mirror: “Nosedive.” The descriptive analysis method was applied in this study. The information used was taken from Charlie Broker's movie scrip. The findings revealed four types of referring expressions, including pronouns (37.5%), proper nouns (25%), indefinite noun phrases (18.75 %), and definite phrases (18.75%). On the other hand, there are three types of meaning: contextual meaning (37.5%), grammatical meaning (37.5 %), and lexical meaning (25%).